Review of the book Children's Languages: other ways of reading - Márcia Buss Simão (Universidade Federal de Santa Catarina, 2005)
This book is the first of two volumes that make up the publication of Language in Education Seminar III Child performed during the 14th COLE in July 2003. The book deals with issues related to education of children in a non-anticipatory of schooling and not marked by the preparation for the elementary school. Discussion focuses on the education of children 0 to 6 years of age and not the education. It consists of articles that provide research, thoughts and experiences involving the different languages of children.